Left–right dewlap asymmetry and phylogeography of Anolis lineatus on Aruba and Curaçao. (24th July 2013) - Gartner, Gabriel E. A.; Gamble, Tony; Jaffe, Alexander L.; Harrison, Alexis; Losos, Jonathan B.
Abstract : Anolis lizards exhibit a remarkable degree of diversity in the shape, colour, pattern and size of their dewlaps. Asymmetry, where one side of the dewlap differs in pattern or colour from the other, has only been reported in one species, Anolis lineatus, and then on only one of the two islands from which it occurs. Given the importance of the dewlap in intra‐ and interspecific signalling, we expanded on previous work by (1) investigating whether the reported asymmetry actually occurs and, if so, whether it occurs on animals from both Aruba and Curaçao; (2) examining whether populations differ in other aspects of their morphology or ecology; and (3) resolving the evolutionary relationships and the history of the two populations. We confirmed the presence of the asymmetrical dewlap on Curaçao and found that the asymmetry extends to populations on Aruba as well. Animals on Curaçao were smaller overall than populations from Aruba with relatively shorter metatarsals, radii, and tibias but relatively deeper heads, longer jaws, and wider and more numerous toepads on fore and hind feet. Habitat use did not differ significantly between the islands. We found populations on Aruba and Curaçao to be reciprocally monophyletic with an early Pleistocene divergence of populations on the two islands. Neutrality tests indicate that neither population has seen any recent reduction in population size, making it unlikely that the asymmetry is a result of founder effects or is some other consequence of reduced genetic variation. A variety of factors likely account for the remarkable and unique dewlap morphology exhibited by this species, although more detailed field studies are required to test these hypotheses. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 409–426.